A competência do profissional de internação domiciliar - Bomfim, Rosa Amorim (2009)
The competence professional of home care is linked with the entirety of knowledge, kills and attitudes to care and better quality of life for users and families. Questioned the competence of these professionals to provision of home care. This study has as general objective to verify the professional competence in the provision of home care. Followed by specific objectives are: to understand the professional competence, to understand the services of home care and to identify the knowledge, skills and attitudes of professional home care. To the greeting these objectives, to make use of a structured methodology in two stages. The first stage consists of a theoretical approach to home care, developed from a literature search. The second stage is a study of the competence of the health professional which acts in home care service, provided by a private health organization, the VITALMED, located in Salvador, Bahia. To the development of this study, to make use as an instrument of data collection a questionnaire with open and closed questions. It divides the data analysis of closed and open questions in three groups the knowledge, skills and attitudes to get the points that guide the relationship between health professionals, users and their families. The analysis of these data, based on the theoretical framework, permitted to identify the competence professionals of home care. These survey results point to innovation in the training of professionals in home care indicating that the competence professionals are the principal factor for quality and efficiency in services. Thus, the verification of these competences can contribute to the excellence of the services home care and the qualification management of those services